Digital Transformation in Tourism: Capturing the Perspective of a Travel Agency - Liyushiana Liyushiana; Agung Edi Rustanto; Maria Ulfah; Ryan Aldiansyah Akbar; Imran Imran (STMIK Dharma Wacana, 2022)
This study aims to investigate the attitude of travel entrepreneurs toward digital transformation in tourism and assess the digital transformation-related actions of travel agency. Qualitative research methodologies were employed in this context, and semi-structured interviews were used to collect data. The data collected from the participants were analyzed using a descriptive technique. According to the research findings, digital transformation will substantially contribute to the tourism industry, including travel agencys, giving a new and crucial alternative for the tourism industry to promote digital transformation. In addition, it has been discovered that there may be obstacles throughout the shift to digital transformation, notably in transmitting innovation to employees and customers. However, in addition to this work, which focuses on the entrepreneur's perspective, it has been suggested that research related to digital tourism can be conducted from the customer's perspective and that various studies can be conducted so that accommodation businesses can transfer digital applications within their companies to customers with the appropriate marketing and advertising effectiveness. In this instance, digital application in travel agency takes the shape of product transformation with the application of virtual tours and the application of new technologies in acquiring information and making business decisions via the TOE Framework.